Optimal doses of high-intensity interval training in patients with coronary artery disease and heart failure: a systematic review and meta-analysis - Wu, Yue; Wang, Hong (Frontiers in Cardiovascular Medicine, 2026)
ObjectiveThis systematic review and meta-analysis aimed to determine the optimal exercise dose parameters of High-Intensity Interval Training (HIIT)—including frequency, total training period, session duration, recovery intensity, and number of sessions—for patients with coronary artery disease (CAD) or heart failure (HF), and to evaluate its effects on peak oxygen uptake (VO2peak) and oxygen consumption at the first ventilatory threshold (VO2 at VT1).MethodsRandomized controlled trials (RCTs) investigating HIIT in CAD or HF patients and reporting VO2peak and/or VO2 at VT1 were identified by searching seven databases. The Cochrane RoB2 tool and RevMan 5.4 software were used for risk-of-bias assessment and statistical analysis.ResultsNineteen RCTs involving 1,152 patients (HIIT: n = 571; control: n = 581) were included. HIIT significantly improved VO2peak in both CAD patients (+1.69 mL·kg−1·min−1, 95% CI: 1.02–2.35, P < 0.00001) and HF patients (+2.46 mL·kg−1·min−1, 95% CI: 0.64–4.28, P = 0.008), with a greater improvement observed in HF. VO2 at VT1 also significantly increased in CAD (3 studies, n = 501: +0.97 mL·kg−1·min−1, 95% CI: 0.39–1.56, P = 0.001; I2 = 34%) and HF (5 studies, n = 112: +1.39 mL·kg−1·min−1, 95% CI: 0.23–2.56, P = 0.02; I2 = 0%). Subgroup analyses indicated that improvements in VO2peak were influenced by patient characteristics and exercise parameters. For CAD, greater benefits were associated with single-session duration >35 min, ≥36 sessions, and total training period ≥12 weeks. For HF, benefits were linked to single-session duration >35 min and frequency ≥3 days/week. Heterogeneity was moderate for CAD (I2 = 45%) and high for HF (I2 = 79%), suggesting variations related to study design and HIIT protocols.ConclusionHIIT effectively improves VO2peak in both CAD and HF patients, with potentially greater benefits in HF. Dose-response analysis provides preliminary insights into its effect on submaximal exercise capacity (VO2 at VT1). Optimal parameters are: for CAD—frequency ≥2 days/week, total period ≥12 weeks, session duration >35 min, active recovery intensity ≥40% VO2peak, work/rest ratio 0.5–1.33; for HF—frequency ≥3 days/week, total period ≥12 weeks, session duration >35 min, active recovery intensity ≥40%, work/rest ratio 0.5–1.